2022
DOI: 10.1002/geot.202100065
|View full text |Cite
|
Sign up to set email alerts
|

Current developments of digital ground modelling in tunnelling

Abstract: This article analyses and discusses the current state of the art in the development of digital ground models in tunnelling. Following a review and discussion of the literature research combined with interview responses, a deficit analysis was performed. It shows why current projects mainly work with models and software that function as isolated solutions. A lack of software developments and limited collaborative work mean that the effects of current findings cannot immediately be implemented in models. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The study also mentions other problems, such as disorganized management and difficulties in integrating it with geographic information systems (GISs). Exenberger et al [39] conducted a study on digital terrain modeling for tunneling using a combination of literature review and interviews with 20 industry professionals. The study found that many current projects rely on standalone models and software due to limited collaboration and insufficient software development.…”
Section: Bim Adoption In Complementary Road Structuresmentioning
confidence: 99%
“…The study also mentions other problems, such as disorganized management and difficulties in integrating it with geographic information systems (GISs). Exenberger et al [39] conducted a study on digital terrain modeling for tunneling using a combination of literature review and interviews with 20 industry professionals. The study found that many current projects rely on standalone models and software due to limited collaboration and insufficient software development.…”
Section: Bim Adoption In Complementary Road Structuresmentioning
confidence: 99%
“…The Tunnelpixel is the central means of information transfer. 8 Following this approach, various research has been developed, especially focusing on ground model development with the CAD-and interpolation-based approach. The aim is to uniformly break down ground specific information along the alignment using the concept of the Tunnelpixel.…”
Section: Developments At University Of Innsbruckmentioning
confidence: 99%
“…Furthermore, complicated model adaptations are avoided even after changes in the course of the planning process. The Tunnelpixel is the central means of information transfer 8 …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding social sustainability in the field of TIM, our approach primarily focuses on the structures and work within a team or small group. We therefore utilise our findings from a qualitative study on the topic of current developments within BIM in tunnelling [7]. With respect to economic sustainability, our focus is mostly based on evaluating the improved use of resources, which might as well result from an increased social sustainability.…”
Section: Introductionmentioning
confidence: 99%